Situational analysis and future directions for medicine retail outlets: compliance with pharmaceutical regulatory standards in Ethiopia - Yesuneh Tefera Mekasha; Habtamu Getahun; Addisu Afrassa Tegegne; Gemmechu Hasen; Gemmechu Hasen (Frontiers in Medicine)
BackgroundMedicine regulation is essential for safeguarding the safety, efficacy, and quality of pharmaceutical products available in medicine retail outlets (MROs). It ensures that medicines, whether sourced locally or internationally, comply with stringent quality standards and regulatory protocols to protect public health. Effective regulation enhances trust in pharmaceutical markets by ensuring the availability of safe and effective medications. However, the regulatory framework within healthcare facilities, particularly in MROs where significant drug-related information is exchanged, is often underperforming. This issue is particularly pronounced in low-and middle-income countries like Ethiopia, where MROs play a critical role as the initial point of healthcare contact. This review aims to assess the level of compliance with pharmaceutical regulatory standards in medicine retail outlets (MROs) in Ethiopia and to evaluate the enforcement of these standards in the country’s pharmaceutical market.MethodsThe review utilized online databases such as PubMed, and Web of Science to collect relevant studies and reports. It focused on issues of regulatory compliance in MROs in Ethiopia, identifying gaps in practice, drug quality, and adherence to national guidelines set by the Ethiopian Food and Drug Authority (EFDA).ResultsThe review revealed significant regulatory compliance issues within Ethiopian MROs, leading to the distribution of poor quality medicines. It was found that drugs obtained from non-compliant outlets failed to meet quality control standards outlined in drug monographs. Many MROs and pharmacy professionals were found to be non-compliant with EFDA guidelines. Additionally, dispensing and storage practices in MROs were not in line with EFDA regulations and required improvements.ConclusionThe review underlines the need for regulatory enforcement in Ethiopia health settings to address issues of non-compliance and the distribution of poor-quality drugs. It suggests that regulatory bodies should enhance inspection measures and provide opportunities for continued professional development for pharmacy staff and regulatory personnel. Collaboration among regulatory authorities, government, professionals, and academic researchers are pivotal to improving compliance and ensuring the availability of safe, effective, and quality medicines within medicine retail outlets and then protecting public health.